Antimicrobial Activity of Ethanolic Extract of Leaves of Tabebuia rosea (Bertol.) DC. - Sakthi Saravanan, V.; Shanmugap, P.; Mohamed Ali, G.; Manoj Kumar, R.; Manik, T.; Neelima, M.; Madhavi, K. (Asian Journal of Chemistry, 2011)
Tabebuia rosea (Bertol.) DC. is commonly grown as an ornamental tree for its grand and majestic pink or purple flowers which offer different shades of colours. The wood is valuable and used in the manufacture of furniture. The preliminary phytochemical screening of the leaves revealed the presence of saponins, tannins, flavonoids and alkaloids. In vitro antibacterial studies on the ethanolic extracts of leaves were carried out on Staphylococcus aureus, Staphylococcus epidermidis, Klebsiella pneumoniae, Escherichia coli and Candida albicans by using agar disc diffusion method. The microbial strains were exposed to concentration of 100 μg/disc, with ethanol as solvent. The results of present antimicrobial assay revealed that the extract showed good inhibitory activity against all the tested pathogens compared with standard antibiotics like ciprofloxacin and ketoconazole. The inhibitory activities were found to be dose dependent.